UNESCO Experts’ Meeting on the Safeguarding of Syria’s heritage: Berlin, 2-4 June 2016 - Munawar, Nour A. (Ex Novo: Journal of Archaeology, 2017)
Armed conflicts are one of the primary reasons that endanger heritage and the symbolic value of cultures. Both the protection of cultural legacy and the promotion of the plural interests and identities that intersect and construct heritage in times of war should be reinforced with an effi-ient strategy and effective actions. The unprecedented destruction of renowned cultural heritage sites in Syria has not remained unnoticed. The contentious violations that occurred during the hostilities of Syria’s ongoing conflict have drawn the attention of international organisations such as UNESCO, ICOMOS, ICCROM, and ICOM. Following the constant media reports and aerial photos of heritage destructions in Syria, UNESCO held an experts’ meeting in Berlin to discuss its safeguarding. The meeting was envisioned as a follow-up to the implementation of the UNESCO action plan for the Emergency Safeguarding of Syria’s Cultural Heritage (UNESCO 2014). The three-day conference (2 - 4 June 2016) aimed to continue the work of the 2014 Paris conference, supported by the three-year EU-funded project on the Emergency Safeguarding of the Syrian Cultural Heritage.